The Existence of the Aceh Reintegration Board in Fulfilling the Constitutional Rights of Conflict Victims in Aceh - Febrina, Maya; Husni Husni; Nurdin Nurdin (International Journal of Sociology and Law, 2026)
The armed conflict in Aceh between the Free Aceh Movement (GAM) and the Government of the Republic of Indonesia for more than three decades had caused serious humanitarian impacts, including various forms of human rights violations against civilians. The signing of the Helsinki Memorandum of Understanding (MoU) on 15 August 2005 marked a turning point in conflict resolution, subsequently implemented through Law Number 11 of 2006 on the Governance of Aceh and Aceh Qanun Number 6 of 2015 on the Aceh Reintegration Board (BRA). This study aims to analyze the legal regulatory construction regarding the position and authority of BRA in fulfilling the constitutional rights of conflict victims, examine legal certainty in its implementation, and formulate an ideal regulatory concept. The research method used is normative juridical with statutory and conceptual approaches. Secondary data were collected through literature studies supported by interviews with relevant informants. The results show that the legal regulatory construction regarding the position and authority of BRA has not fulfilled substantive justice due to the absence of technical norms and the suboptimal integration between legal structure and substance. Legal uncertainty has impacted the unfulfilled constitutional rights of conflict victims, reflected in the replacement of the recovery scheme with a social assistance scheme, the absence of standard operating procedures (SOP), and unsynchronized conflict victim data. The ideal regulatory concept requires comprehensive legal reconstruction through strengthening the institutional position of BRA, establishing operational implementing regulations, and strengthening oversight and accountability systems.